Peran Organisasi Kemasyarakatan Pemuda dalam Pelaksanaan Asian Games 2018: Studi tentang Pemuda Pancasila Kota Palembang - Amalia, Fadila Nur; Muradi, Muradi; Bainus, Arry (Tapis: Jurnal Penelitian Ilmiah, 2019)
In 2018, Palembang became one of the hosts of the biggest sports event in Asia, that’s the Asian Games. As a civil society, the youth community organization is a driving force for the functioning of the social system. This paper explores the role of Pemuda Pancasila as youth community organizations in the success of Asian Games 2018. This study employed descriptive qualitative methods to explore the research objectives. The results showed that Pemuda Pancasila Pelembang conducted peaceful actions to anticipate events which could impact the success of Asian Games 2018, and appealed to the public to contribute to the success of this event through mass and electronic media, furthermore to help maintain security during the Asian Games 2018 event.